Islamic Education Teachers’ Role in Cultivating Religious Moderation among Students - Ikhfak Nurfahmi; Ajahari Ajahari; Surawan Surawan (Jurnal Indonesia Studi Moderasi Beragama, 2025)
Background: The role of Islamic religious education teachers in fostering religious moderation among students has become increasingly urgent in today's diverse and dynamic social environment. Objective: This study aims to determine the urgency of the role of Islamic religious education teachers in fostering religious moderation in students at school. Method: The research uses a qualitative approach with a qualitative descriptive method. It was conducted at SMK Karsa Mulya Palangka Raya in 2024. The research subjects include religious education teachers, principals, subject teachers, and students. Data collection was carried out through observation, interviews, and documentation. The process of data validation used triangulation. Result: Religious moderation in students can be successfully instilled through collaboration between religious education and subject teachers, supported by the principal and regulations that promote religious moderation. Conclusion: Religious moderation coaching is more effective when there is a cohesive effort between various school stakeholders, including teachers and principals. Effective communication and a supportive school environment are key to promoting religious moderation in students. Contribution: This research contributes to understanding the role of Islamic religious education teachers in fostering religious moderation in schools and emphasises the importance of collaboration and institutional support in achieving this goal.